Rapport de validation du programme d'accélération de l'élevage sensible au genre-chaine de valeur lait - Siagbe, Golli; Derenoncourt, Marie Ena Pascale; Atadokpede, Marine; Ouedraogo, Issa (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
The implementation of an acceleration program requires a participatory and inclusive approach to determining objectives, business selection criteria, and training content, as well as identifying opportunities for collaboration. For the Gender Smart Livestock Accelerator (GSLA), led by the Alliance Bioversity & CIAT Alliance in collaboration with ILRI under the AICCRA program, the program design was finalized through a one-day validation workshop attended by nearly 30 resource persons. This workshop refined the program’s objectives, areas of intervention, training content, and potential partnerships for delivering training and financing companies. Prior to the workshop, stakeholder consultations were held from the last quarter of 2024 until April 2025, to gather their opinions on the program, identify the training modules, and define collaboration areas. Participants in the program include Individuals, Sole Proprietorships, Single-member, Limited Liability Company, Cooperatives, and Economic Interest Groups operating throughout the dairy value chain. The selected training modules are: